2014
DOI: 10.1016/j.cocom.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the finite-temperature anisotropic elastic and thermal properties of Ge3N4: A first-principles study

Abstract: a b s t r a c tTotal energy calculations of germanium nitride, done at three different phases under extreme conditions in the b, wII and g structures using the plane-wave pseudo-potential method plus GGA-PBE in the framework of quantum mechanical density functional theory. Bulk properties such as the equilibrium lattice parameters, elastic constants and bulk moduli are predicted and compared to available theoretical and experimental data. g-Ge 3 N 4 could not resistant to thermal shocks due to its brittleness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
3
6
0
Order By: Relevance
“…Since K ′ 0 is the pressure derivative of the isothermal bulk modulus, the present wider experimental pressure range can be beneficial for the determination of the K ′ 0 . The present K 0 value of γ‐Ge 3 N 4 is smaller than that determined by a previous experimental study, while the present value is consistent with theoretical predictions . Further studies such as sound velocity measurements by the pulse echo method and/or Brillouin spectroscopy are required to determine the elastic properties of γ‐Ge 3 N 4 .…”
Section: Resultssupporting
confidence: 75%
“…Since K ′ 0 is the pressure derivative of the isothermal bulk modulus, the present wider experimental pressure range can be beneficial for the determination of the K ′ 0 . The present K 0 value of γ‐Ge 3 N 4 is smaller than that determined by a previous experimental study, while the present value is consistent with theoretical predictions . Further studies such as sound velocity measurements by the pulse echo method and/or Brillouin spectroscopy are required to determine the elastic properties of γ‐Ge 3 N 4 .…”
Section: Resultssupporting
confidence: 75%
“…Wang et al [ 17 ] found that γ -Ge 3 N 4 could retain its stability up to 69.2 GPa at room temperature. The critical pressure of the β → wII phase transition was 10.7 GPa (at 300 K), and the β → wII transformation occurred at 13.5 GPa and 1100 K; further compression led to the wII → γ transition at 35.7 GPa, as reported by Luo et al [ 18 ] In addition to silicon nitride and germanium nitride, IV A Group and V A Group elements compounds have been investigated, such as Si 3 P 4 and Ge 3 P 4 [ 19 , 20 , 21 ], W 3 N 4 [ 22 , 23 , 24 ], BN [ 25 , 26 , 27 , 28 , 29 , 30 ] and C 3 N 4 [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionsupporting
confidence: 70%
“…The second-order elastic constants and mechanical moduli of γ-M 3 N 4 are obtained from DFT calculations and listed in Table 1 . The data from previous works are also included 15 , 17 , 18 . The elastic constants and mechanical properties of these two nitrides are slightly smaller than the reported experimental and theoretical results due to the overestimated lattice parameter where GGA is implemented in the calculations.…”
Section: Resultsmentioning
confidence: 99%